Durability and effectiveness of dual vs. triple therapy and tablet simplification in ART: findings from the Italian MOSAICO study - Mengato, Daniele; Berti, Giacomo; Francavilla, Andrea; Michielan, Silvia; Cappellazzo, Linda; Agnoletto, Laura; Silvani, Maria Chiara; Chiumente, Marco; Gregori, Dario; Mazzitelli, Maria; Venturini, Francesca; Cattelan, Anna Maria; et al. (Frontiers in Pharmacology, 2025)
IntroductionTreatment optimization in people with HIV (PWH) has increasingly focused on reducing drug burden and improving regimen simplicity. However, comparative real-world evidence on dual therapy (DT) vs. triple therapy (TT), and single-tablet regimens (STR) vs. multi-tablet regimens (MTR), remains limited.MethodsThe MOSAICO study is a multicenter, retrospective observational analysis conducted across 20 centers, including people with HIV on a stable virological suppression who switched antiretroviral therapy between 2017 and 2019. People were followed-up up to 48 months post-switch. Comparative analyses assessed virological suppression (HIV-RNA <50 copies/mL), CD4+ T cell count, CD4/CD8 ratio, and treatment discontinuation. Propensity score weighting was applied to adjust for baseline differences.ResultsFour hundred ninety-one PWH were included. Both DT and triple therapy groups maintained high levels of virological suppression over 48 months (12 months: 97.1% vs. 91.6%; 24 months: 100% vs. 95.6%; 36 months: 100% vs. 96.9%; 48 months: 100% vs. 100%). From 24 months onward, all persons living with HIV remaining on their respective regimens achieved full virological suppression. Immunological recovery (CD4+ count and CD4/CD8 ratio) was comparable across groups, although TT and MTR groups showed greater increases from lower baselines. STRs demonstrated significantly greater treatment durability than MTRs (aHR = 0.56, 95% CI: 0.32–0.97; p = 0.039), while no significant difference in persistence was found between DT and TT. INSTI-based regimens were predominant in DT and MTR arms (DT vs. TT: 84% vs. 46.52%, p < 0.01; MTR vs. STR: 59.38% vs. 47.14%, p < 0.01).DiscussionThe real-world effectiveness of both dual and triple therapies when tailored to appropriate person profiles. STRs offer enhanced long-term persistence compared to MTRs, supporting treatment simplification strategies. These results reinforce the importance of individualized treatment approaches balancing clinical effectiveness with person-centered considerations such as pill burden and tolerability. Limitations include the retrospective design and the lack of quality-of-life data, which may affect interpretation of patient-centered outcomes. Future efforts should expand access to dual-agent STR to further improve Antiretroviral Therapy outcomes.